2017
DOI: 10.1590/1980-5918.030.002.ao09
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of patients with fibromyalgia syndrome

Abstract: Introduction:The new diagnostic criteria for fibromyalgia (FM) include the presence of chronic, widespread pain associated with other symptoms such as fatigue, sleep disturbance, anxiety and depression. All these symptoms should be considered when thinking and clinical decision making of physiotherapists dealing with FM. However, it is clear that the other symptoms that accompany the pain are often neglected. Objective: To measure the levels of fatigue, sleep disturbances, anxiety and depression in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
2
0
12
Order By: Relevance
“…A depressão foi o transtorno mental com a maior frequência nos artigos, sendo citada em 13 artigos (Goulart, Pessoa & Lombardi-Junior, 2015;Pernambuco, Silva, Fonseca, Reis & D'Ávila, 2017;Freitas, Andrade, Spyrides, Micussi & Sousa, 2016; Ali, Sanches, Lauretti ou concomitantemente, mas sem poder afirmar causa e efeito entre eles (Dias, Marques, Bettini e Paiva, 2017;Terzi, Terzi e Kale, 2015).…”
Section: Depressãounclassified
See 3 more Smart Citations
“…A depressão foi o transtorno mental com a maior frequência nos artigos, sendo citada em 13 artigos (Goulart, Pessoa & Lombardi-Junior, 2015;Pernambuco, Silva, Fonseca, Reis & D'Ávila, 2017;Freitas, Andrade, Spyrides, Micussi & Sousa, 2016; Ali, Sanches, Lauretti ou concomitantemente, mas sem poder afirmar causa e efeito entre eles (Dias, Marques, Bettini e Paiva, 2017;Terzi, Terzi e Kale, 2015).…”
Section: Depressãounclassified
“…(Dias, Marques, Bettini e Paiva, 2017;Terzi, Terzi & Kale, 2015;Işık-Ulusoy, 2019;Danet, Prieto--Rodríguez, Valcárcel-Cabrera & March-Cerdà, 2016;Nieto, 2015). O nível de depressão apresentou correlação com a gravidade dos sintomas da dor (Terzi, Terzi & Kale, 2015;Işık-Ulusoy, 2019) e pode piorar a percepção de sintomas da doença, reduzindo a qualidade de vida do sujeito (Pernambuco, Silva, Fonseca, Reis & D'Ávila, 2017;Alves et al, 2016;Horta-Baas & Romero-Figueroa, 2019;Cabrera, Martín-Aragón, Terol, Núñez & Pastor, 2015), podendo gerar prejuízos na vida sexual (Freitas, Andrade, Spyrides, Micussi & Sousa, 2016). Isso evidencia a importância de o psicólogo e outros profissionais de saúde avaliarem a adesão ao tratamento, e da realização de trabalhos multidisciplinares, visto que somente uma forma de tratamento não é suficiente para dar conta da complexidade da enfermidade, conforme destacam Perissinotti e Sardá-Junior (2019).…”
Section: Ansiedadeunclassified
See 2 more Smart Citations
“…In a study of patients with FMS, it was observed that the PFS scores were correlated with depression, anxiety, and poor quality of sleep .…”
Section: Revised Piper Fatigue Self‐report Scale (Pfs‐r)mentioning
confidence: 99%